Structure of the Bacterial Sex F Pilus Reveals an Assembly of a Stoichiometric Protein-Phospholipid Complex - Costa,TRD; Ilangovan,A; Ukleja,M; Redzej,A; Santini,JM; Smith,TK; Egelman,EH; Waksman,G (CELL, 2016)
Conjugative pili are widespread bacterial appendages that play important roles in horizontal gene transfer, in spread of antibiotic resistance genes, and as sites of phage attachment. Among conjugative pili, the F “sex” pilus encoded by the F plasmid is the best functionally characterized, and it is also historically the most important, as the discovery of F-plasmid-mediated conjugation ushered in the era of molecular biology and genetics. Yet, its structure is unknown. Here, we present atomic models of two F family pili, the F and pED208 pili, generated from cryoelectron microscopy reconstructions at 5.0 and 3.6 Å resolution, respectively. These structures reveal that conjugative pili are assemblies of stoichiometric protein-phospholipid units. We further demonstrate that each pilus type binds preferentially to particular phospholipids. These structures provide the molecular basis for F pilus assembly and also shed light on the remarkable properties of conjugative pili in bacterial secretion and phage infection.